PREFERENSI PERMODALAN PEDAGANG PASAR WAGE PURWOKERTO, PENGUATAN DESTINASI KEUANGAN DAN PERBANKAN SYARIAH VIS A VIS RENTENIR DI PASAR TRADISIONAL - Hilyatin, Dewi Laela (Fakultas Ekonomi dan Bisnis Islam (FEBI), Institut Agama Islam Negeri (IAIN) Purwokerto, 2019)
In developing a business, one of the main instruments is capital. Adequacy of capital can create a problem for business actors including traditional market traders. The many sources of capital in the community cause traders to make preferences in determining the right source of capital. Among the capital sources that are still developing among the community, especially the Wage market traders, are moneylenders. Moneylenders are still an alternative choice for wage market traders with an amount of 11%, because of several things including: ease in the loan process, without conditions, unlimited space and time. But even that convenience is inseparable from the problems that have arisen. Therefore, the government, in this case the OJK, has made several efforts to protect the public from loan sharks through the OJK education magazine, pamphlets, banners, and direct socialization to the public. To strengthen the destination of banks or non-bank financial institutions, 8 strategies and 1 monitoring and evaluation need to be adopted from the strategy of strengthening tourist destinations by BI, OJK, local governments.